2011
DOI: 10.1038/ajh.2011.4
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Prevents Hypertension and Increases Exercise Capacity in Rats With Fructose-Induced Hypertension

Abstract: Taurine supplementation in combination with exercise prevents hypertension and increases exercise capacity by possibly antioxidation and maintaining NO concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…One of the most studied interventions is that of the amino acid taurine with a number of studies reporting beneficial effects of taurine supplementation in the setting of fructose-induced metabolic disorders [8487]. Taurine has been shown to prevent hypertension and increase exercise capacity in rats with fructose-induced hypertension, possibly via antioxidation and maintenance of nitric oxide concentrations [88, 89]. Using a model of 25% fructose intake, it has been shown that taurine and L-arginine have synergistic effects on attenuating insulin resistance hypertension [90].…”
Section: Countering the Adverse Metabolic Effects Of Fructosementioning
confidence: 99%
“…One of the most studied interventions is that of the amino acid taurine with a number of studies reporting beneficial effects of taurine supplementation in the setting of fructose-induced metabolic disorders [8487]. Taurine has been shown to prevent hypertension and increase exercise capacity in rats with fructose-induced hypertension, possibly via antioxidation and maintenance of nitric oxide concentrations [88, 89]. Using a model of 25% fructose intake, it has been shown that taurine and L-arginine have synergistic effects on attenuating insulin resistance hypertension [90].…”
Section: Countering the Adverse Metabolic Effects Of Fructosementioning
confidence: 99%
“…Furthermore, Rahman et al (40) showed that skeletal muscle NO is significantly reduced in rats that consumed food containing 43.6% fructose for 4 wk and that swimming exercise failed to normalize NO levels. It is therefore possible that the observed attenuation of the epigenetic modifications by exercise in fructose-fed rats might have arisen from the effects of fructose on eNOS.…”
Section: E281mentioning
confidence: 99%
“…16 Recent animal and human studies have shown that taurine supplementation lowers BP and improves vascular function, possibly through suppression of renin-angiotensin-aldosterone system activity, 17,18 augmentation of kallikrein activity in the blood and peripheral tissues, 19 suppression of the renal sympathetic nervous system, 9,20 diuretic and natriuretic activities, and vasorelaxant activity. 21 H 2 S can regulate vascular tone through several mechanisms, such as acting on ATP-sensitive potassium channels. [22][23][24] A recent study has found that H 2 S also affects transient receptor potential channels (TRPCs) in mesenchymal stem cells and regulates calcium homeostasis.…”
mentioning
confidence: 99%